Relationship between Regional Socio-Economic Development and Corporate Ratings of Russian Companies - Makeeva, Elena Yu.; Ivashkovskaya, Irina V.; Ruzhanskaya, Liudmila S.; Popov, Konstantin A. (Economy of Regions, 2021)
The search for new sources of regional development is important due to the slowdown in economic growth and the need to shift the emphasis of industrial policy from the macro level to the level of regions and individual companies. In this regard, we consider the participation of companies in reputation ratings as a new source for increasing the investment attractiveness of regions. Additionally, we examine the relationship between corporate and regional ratings: corporate ratings demonstrate a company’s compliance with the sustainable development goals, which, in turn, improves the socio-economic performance of regions. We revealed the positive influence of high corporate ratings on the socio-economic development of regions, opening a new area for interdisciplinary research combining corporate finance and regional economics. On the example of 130 biggest Russian public non-financial companies, we obtained several significant results that allow determining the impact of corporate ratings on the socio-economic situation of regions and corporate financial performance. The ratings include Sustainable development Index of the Russian Union of Industrialists and Entrepreneurs (RUIE), Environmental responsibility rating of the World Wildlife Fund (WWF) Russia, and Corporate social responsibility rating of the Association of Managers of Russia (AMR). The calculations showed that the participation of companies in the ratings of WWF Russia and RUIE positively affects the indicators sustainable development of regions where these companies are located. Simultaneously, the influence of companies’ participation in the rating of WWF Russia is higher than the influence of participation in the RUIE rating. In addition, reputation ratings have a positive impact on the return on assets and market capitalisation of Russian companies. Thus, we proved that participation in corporate ratings leads to an increase in performance. However, the effects of participation in various ratings differ. For example, to increase its conditions and performance, a company should be a leader of the rating of RUIE and just participate in the rating of WWF Russia. The rating of AMR influences the market capitalisation the most. The obtained findings indicate the need for expanding the participation of Russian companies in corporate ratings and enable research in the field of sustainable development of companies.